2019
DOI: 10.1186/s12931-019-1190-z
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood proteomic profiling of idiopathic pulmonary fibrosis biomarkers in the multicentre IPF-PRO Registry

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive lung disease for which diagnosis and management remain challenging. Defining the circulating proteome in IPF may identify targets for biomarker development. We sought to quantify the circulating proteome in IPF, determine differential protein expression between subjects with IPF and controls, and examine relationships between protein expression and markers of disease severity.MethodsThis study involved 300 patients with IPF from the IPF-PRO Registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 31 publications
6
52
0
2
Order By: Relevance
“…Evaluating signature components allowed for further investigation of potential proteomic relationships and pathways associated with progression. Our identified signature was enriched for processes involving immune system regulation in non-progressors, which echoes results from other studies 20 , 22 , 23 , and also included 4 of the 6 proteins previously identified in the COMET cohort as an index of IPF progression 20 . The complement cascade has also previously been associated with IPF disease severity 22 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Evaluating signature components allowed for further investigation of potential proteomic relationships and pathways associated with progression. Our identified signature was enriched for processes involving immune system regulation in non-progressors, which echoes results from other studies 20 , 22 , 23 , and also included 4 of the 6 proteins previously identified in the COMET cohort as an index of IPF progression 20 . The complement cascade has also previously been associated with IPF disease severity 22 .…”
Section: Discussionsupporting
confidence: 85%
“…Our identified signature was enriched for processes involving immune system regulation in non-progressors, which echoes results from other studies 20,22,23 , and also included 4 of the 6 proteins previously identified in the COMET cohort as an index of IPF progression 20 . The complement cascade has also previously been associated with IPF disease severity 22 . Interestingly, our identified signature did not include MMP-7, which has been linked to IPF progression in several other studies 21,23,34 , though some proteins in our signature did have proteolytic function (legumain, PSD7).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The IPF-PRO registry, a multicenter cohort study, analyzed over 1300 proteins in peripheral blood of patients with IPF and compared them to healthy controls, identifying nine proteins that accurately distinguished patients with IPF from controls. The circulating proteome differed for apolipoprotein A-1 (APOA1), complement C1r subcomponent, intracellular adhesion molecule 5 (ICAM5), C-C motif chemokine 18, 14-3-3 protein sigma (SFN), sonic hedgehog protein, oxidized low-density lipoprotein receptor 1, matrix metalloproteinase 3 (MMP3), macrophage-capping protein, and heat shock protein 90 beta-1 (HSP90β1) [49] (Table 1). Even though the profile of circulating proteins differs from lung proteins, it can still provide insight into biological pathways linked to a persistent overexpression of inflammatory markers, adhesion molecules, complement proteins and HSPs.…”
Section: Proteomic Analysis In Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…Transcriptomics studies of patients with IPF have demonstrated that transcriptional changes are involved in the pathophysiologic mechanisms of these diseases (Yang et al, 2007;Zuo et al, 2002). Genes that are differentially expressed in different groups are almost always associated with a particular disease phenotype (Huang et al, 2015;Konishi et al, 2009;Todd et al, 2019). Yang and colleagues (2013) analyzed the transcriptional profiles of lung tissue, collected from IPF patients and non-diseased controls, and found that the elevated expression of cilium genes was associated with more extensive microscopic honeycombing.…”
Section: Introductionmentioning
confidence: 99%